2011
DOI: 10.3855/jidc.971
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of azithromycin in Salmonella isolates from Pakistan

Abstract: Introduction: Enteric fever is caused by Salmonella enterica serovars Typhi and Paratyphi A, B and C. It is a significant public health issue in Pakistan, which is exacerbated by a high level of resistance some isolates display to drugs routinely used in treatment. Azithromycin may be a treatment option for such isolates. Methodology: We determined the minimum inhibitory concentrations (MICs) of Salmonella Typhi and Paratyphi isolates against azithromycin in an attempt to gauge its feasibility as a therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…causes salmonellosis, among other diseases and are also predominant cause of human foodborne outbreaks and diseases in tropical and sub-tropical countries leading to public health threats [1]. In order to facilitate treatment, recommended therapeutic regimen for Salmonella infections were based on the use of ampicillin, chloramphenicol and trimethoprim/ sulfamethoxazole [2], however there had been the emergence of resistance resulting in great impairment of the efficacy of these antibiotics treatment options [3].…”
Section: Introductionmentioning
confidence: 99%
“…causes salmonellosis, among other diseases and are also predominant cause of human foodborne outbreaks and diseases in tropical and sub-tropical countries leading to public health threats [1]. In order to facilitate treatment, recommended therapeutic regimen for Salmonella infections were based on the use of ampicillin, chloramphenicol and trimethoprim/ sulfamethoxazole [2], however there had been the emergence of resistance resulting in great impairment of the efficacy of these antibiotics treatment options [3].…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella Typhi and Paratyphi A and C isolates had a mean inhibitory concentration (MIC) of azithromycin that indicates it could be utilised for therapeutic purposes. 12 A study conducted in 2009 suggests that fluoroquinolones (ciprofloxacin, ofloxacin) and azithromycin are almost equal in clinical efficacy in treatment of typhoid fever. 6 However a study conducted in 2011 suggests that fluoroquinolones are found to be superior than other recent antibiotics (azithromycin, cephalosporins).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown by the minimum inhibitory concentration (MIC) of Salmonella Typhi, Paratyphi A and Paratyphi C when they were exposed to azithromycin that it may have promise for use in therapeutic settings. 12 According to the findings of a study that was carried out in 2009, the clinical efficacy of fluoroquinolones (such as ciprofloxacin and ofloxacin) and azithromycin in the treatment of typhoid fever is practically same. 6 NA Trivedi and others 14 intended to evaluate the quality of the evidence that supports the preference of azithromycin for the treatment of uncomplicated typhoid fever over the other medicines.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The reason for therapeutic response is the high intracellular concentrations achieved by azithromycin of up to 50 to 100 times that in serum. 19,21,22 Despite this, continuing treatment without taking in to consideration the laboratory MIC results is fraught with problems. Although S. Typhi is a predominately intracellular bacteria, it is estimated that one-third of bacterial cells in the blood are extracellular.…”
Section: Discussionmentioning
confidence: 99%